Precision nutrition-based strategy for management of human diseases and healthy aging: current progress and challenges forward - Singh, Vipin Kumar; Hu, Xiao-Hu; Singh, Amit Kishore; Solanki, Manoj Kumar; Vijayaraghavan, Pooja; Srivastav, Rajpal; Joshi, Naveen Kumar; Kumari, Madhuree; Singh, Sandeep Kumar; Wang, Zhen; Kumar, Ajay (Frontiers in Nutrition, 2024)
Currently, the treatment of various human ailments is based on different therapeutic approaches including traditional and modern medicine systems. Precision nutrition has come into existence as an emerging approach considering the diverse aspects such as age, sex, genetic and epigenetic makeup, apart from the pathophysiological conditions. The continuously and gradually evolving disciplines of genomics about nutrition have elucidated the importance of genetic variations, epigenetic information, and expression of myriads of genes in disease progression apart from the involvement in modulating therapeutic responses. Further, the investigations have presented the considerable role of gut microbiota comprising of commensal and symbionts performing innumerable activities such as release of bioactive molecules, defense against pathogenic microbes, and regulation of immunity. Noteworthy, the characteristics of the microbiome change depending on host attributes, environmental factors, and habitat, in addition to diet, and therefore can be employed as a biomarker to unravel the response to given food. The specific diet and the components thereof can be suggested for supporting the enrichment of the desired microbial community to some extent as an important part of precision nutrition to achieve not only the goal of human health but also of healthy aging.